Unravelling post‐transcriptional PrmC‐dependent regulatory mechanisms in Pseudomonas aeruginosa. (24th July 2016) - Krueger, Jonas; Pohl, Sarah; Preusse, Matthias; Kordes, Adrian; Rugen, Nils; Schniederjans, Monika; Pich, Andreas; Häussler, Susanne
Summary: Transcriptional regulation has a central role in cellular adaptation processes and is well investigated. In contrast, the importance of the post‐transcriptional regulation on these processes is less well defined. The technological advancements have been critical to precisely quantify protein and mRNA level changes and hold promise to provide more insights into how post‐transcriptional regulation determines phenotypes. In Pseudomonas aeruginosa the methyltransferase PrmC methylates peptide chain release factors to facilitate translation termination. Loss of PrmC activity abolishes anaerobic growth and leads to reduced production of quorum sensing‐associated virulence factors. Here, by applying SILAC technology in combination with mRNA‐sequencing, they provide evidence that the P. aeruginosa phenotype can be attributed to a change in protein to mRNA ratios of selected protein groups. The UAG‐dependent translation termination was more dependent on PrmC activity than the UAA‐ and UGA‐dependent translation termination. Additionally, a bias toward UAG stop codons in global transcriptional regulators was found. The finding that this bias in stop codon usage determines the P. aeruginosa phenotype is unexpected and adds complexity to regulatory circuits. Via modulation of PrmC activity the bacterial cell can cross‐regulate targets independently of transcriptional signals, a process with an underestimated impact on the bacterial phenotype.